The impact of administration of conjugate vaccines containing cross reacting material on Haemophilus influenzae type b antibody responses in infants: A systematic review and meta-analysis of randomised controlled trials. Issue 34 (25th July 2016) - Voysey, Merryn; Sadarangani, Manish; Clutterbuck, Elizabeth; Bolgiano, Barbara; Pollard, Andrew J.
Abstract: Background: Protein-polysaccharide conjugate vaccines such as Haemophilus influenzae type b (Hib), meningococcal, and pneumococcal vaccine, induce immunological memory and longer lasting protection than plain polysaccharide vaccines. The most common proteins used as carriers are tetanus toxoid (TT) and cross reacting material-197 (CRM), a mutant form of diphtheria toxoid. CRM conjugate vaccines have been reported to suppress antibody responses to co-administered Hib-TT vaccine. Methods: We conducted a systematic review and meta-analysis of randomised controlled trials in which infants were randomised to receive meningococcal or pneumococcal conjugate vaccines along with Hib-TT. Trials of licensed vaccines with different carrier proteins were included for group C meningococcal (MenC), quadrivalent ACWY meningococcal (MenACWY), and pneumococcal vaccines. Results: Twenty-three trials were included in the meta-analyses. Overall, administration of MenC-CRM in a 2 or 3 dose schedule resulted in a 45% reduction in Hib antibody concentrations (GMR 0.55, 95% CI 0.49–0.62). MenACWY-CRM boosted Hib antibody responses by 22% (GMR 1.22, 95% CI 1.06–1.41) whilst pneumococcal CRM conjugate vaccines had no impact on Hib antibody responses (GMR 0.91, 95% CI 0.68–1.22). Conclusions: The effect of CRM protein-polysaccharide conjugate vaccines on Hib antibody responses varies greatly between vaccines. Co-administration of a CRM conjugate vaccine can produce either positive or negative effects on Hib antibody responses. These inconsistencies suggest that CRM itself may not be the main driver of variability in Hib responses, and challenge current perspectives on this issue.